The Effect of Tactile Touch on Changes in Vital Signs in Low Birth Weight Infants (BBLR) in the Nicu Room of Dr. MM Hospital. Dunda Limboto - Ameliya Pratiwi Panigoro; Zuriati Muhamad; Pipin Yunus (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
BBLR is a health problem that is still a major concern in the world, including Indonesia, because BBLR babies have a high risk of experiencing disturbances of physiological functions including the respiratory system, cardiovascular and body temperature regulation which if not above has a serious impact on the baby's condition. The purpose of the study was to determine the effect of tactile touch on changes in vital signs in low-birth weight babies (BBLR) in the NICU room of dr. MM. Dunda Limboto. Quantitative research method with a pre-experiment design with a one-group pre-test and post-test design approach, the population of this study was all BBLR babies, a research sample of 20 infants with purposive sampling technique, the research instrument used a vital sign observation sheet, the data was analyzed by the Wilcoxon test. The results of the study were obtained before being given tactile touch, the majority of hypothermic body temperature was 11 infants (55%) and an average of 36.295OC, normal heart rate was 11 infants (55%) and an average of 153x/minute, and normal oxygen saturation was 15 infants (75%) and an average of 90.90%. After being given tactile touch, the majority of normal body temperature changes in 17 infants (85%) and an average of 36.580OC, normal heart rate of 15 infants (75%) and an average of 148.27x/minute, and oxygen saturation was completely normal in 20 infants (100%) with an average of 94.44%. Then body temperature p=0.036, heart rate p=0.006 and oxygen saturation p=0.000 (? ? 0.05) were obtained. It can be concluded that there is an effect of tactile touch on changes in vital signs in BBLR babies in the NICU room of dr. MM. Dunda Limboto. Therefore, nurses can apply tactile touch in the nursing care of BBLR patients so as to improve nursing services.